Inovasi Digital Marketing UMKM oleh Dinas Koperasi, Usaha Mikro, Perdagangan dan Perindustrian Kabupaten Probolinggo - Putri, Maretha Mufidah; Rusly, Fathullah; Armanto, Nuruddin (Ecobuss, 2024)
Through the use of technology and digitalization, the Probolinggo Regency government created an application innovation in the form of e-commerce called the Integrated MSME Development Management System (SIMADU), with the aim of helping market MSME products and expanding the marketing reach of Probolinggo Regency MSMEs through digital marketing. The research method used is a qualitative descriptive approach with case studies. Data was collected through interviews, observation and documentation. The research results show that implementing innovations such as SIMADU can help accelerate economic recovery, increase the competitiveness of MSMEs in facing competition and improve the economy of MSMEs in Probolinggo Regency. Although in terms of function performance, features and application servers still need evaluation.